2002
DOI: 10.1051/0004-6361:20011747
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas in normal late-type galaxies

Abstract: Abstract. We present 12 CO(J = 1-0) line observations of 22 low-luminosity spiral galaxies in the Virgo cluster. These data, together with 244 others available in the literature, allow us to build a large sample that we use to study the molecular gas properties of galaxies spanning a large range of morphological types and luminosities and belonging to different environments (clusters -field). The molecular gas content of the target galaxies is estimated using a luminosity-dependent X = N(H2)/I(CO) conversion f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
390
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 219 publications
(411 citation statements)
references
References 67 publications
18
390
3
Order By: Relevance
“…We determine the molecular gas masses using the canonical galactic X CO factor of 2.3 × 10 20 cm −2 /K km s −1 of Strong et al (1988) (Table 1, Value Gal ). The conversion factor from CO to H 2 (X CO ) in galaxies depends on the metallicity (Wilson 1995;Israel 1997Israel , 2000Barone et al 2000;Boselli et al 2002;Strong et al 2004;Leroy et al 2005). Boselli et al (2002) studied X CO in normal late-type galaxies and derived X CO factors ranging from 10 20 cm −2 /K km s −1 in giant spirals to 10 21 cm −2 /K km s −1 in dwarf irregulars.…”
Section: The Gas Masses and Metallicitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We determine the molecular gas masses using the canonical galactic X CO factor of 2.3 × 10 20 cm −2 /K km s −1 of Strong et al (1988) (Table 1, Value Gal ). The conversion factor from CO to H 2 (X CO ) in galaxies depends on the metallicity (Wilson 1995;Israel 1997Israel , 2000Barone et al 2000;Boselli et al 2002;Strong et al 2004;Leroy et al 2005). Boselli et al (2002) studied X CO in normal late-type galaxies and derived X CO factors ranging from 10 20 cm −2 /K km s −1 in giant spirals to 10 21 cm −2 /K km s −1 in dwarf irregulars.…”
Section: The Gas Masses and Metallicitiesmentioning
confidence: 99%
“…The conversion factor from CO to H 2 (X CO ) in galaxies depends on the metallicity (Wilson 1995;Israel 1997Israel , 2000Barone et al 2000;Boselli et al 2002;Strong et al 2004;Leroy et al 2005). Boselli et al (2002) studied X CO in normal late-type galaxies and derived X CO factors ranging from 10 20 cm −2 /K km s −1 in giant spirals to 10 21 cm −2 /K km s −1 in dwarf irregulars. They conclude that using a constant X CO factor to derive the molecular gas mass from CO observations could lead to an underestimation of a factor ∼10.…”
Section: The Gas Masses and Metallicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used so far the Galactic solar neighborhood value, but there is ample evidence that X CO varies in other galaxies as a function of physical conditions (e.g. Maloney & Black 1988;Israel 1997;Barone et al 2000;Boselli et al 2002;Israel et al 2003;Israel 2005;Bolatto et al 2008;Narayanan et al 2005;Leroy et al 2011;Shetty et al 2011;Narayanan et al 2012;Bell et al 2007). Thus, we consider an alternative conversion factor, which depends on the metallicity, and varies radially following the metallicity gradient along the disk:…”
Section: Radial Profilesmentioning
confidence: 99%
“…Using the same data of Kenney & Young (1989), Rengarajan & Iyengar (1992) found evidence of a CO deficit in some Virgo spiral, and Vollmer et al (2008) detected in NGC 4522 molecular gas displaced from the galactic disk because of ram pressure. Boselli et al (2002), Fumagalli & Gavazzi (2008) and Fumagalli et al (2009) found a molecular depletion in highly HI deficient galaxies, where the HI is depleted well inside the optical disk. Since not all the HI-deficient galaxies examined in their papers are cluster galaxies, it is of interest to analyze a sample of normal and HI-deficient galaxies in a cluster.…”
Section: Introductionmentioning
confidence: 96%